Preliminary Measurement Properties of the Early Childhood Occupational Profile (ECOPE) - Cary C. Moore (Scholarworks @ WMU, 2021)
Background: This study established the preliminary psychometric properties of the Early Childhood Occupational Profile (ECOPE; Moore & Bowyer, 2018) and investigated the perspectives of occupational therapists on the clinical utility of the tool. Method: An embedded mixed methods research design was used to support the use of different research questions and unique sets of data. National and international occupational therapists administered the ECOPE on video case studies and on children from their caseload. These data were analyzed using the Rasch goodness of fit statistics to evaluate the validity and reliability of the ECOPE. The participating occupational therapists also completed an anonymous survey to gather information on the clinical utility of the tool. Results: The Rasch goodness of fit statistics indicated the ECOPE strongly measures the construct of occupational participation and reliably detects differences in young children's occupational participation skills. Qualitative data from occupational therapists indicated the ECOPE has strong clinical utility and a positive impact on treatment planning. Conclusion: This study established the preliminary reliability, validity, and clinical utility of the ECOPE. The ECOPE is an occupation-based assessment that reflects the distinct value of occupational therapy while evaluating the young child's occupational participation skills in the natural contexts of home or community.